The VLT Survey Telescope ATLAS. Issue 4 (30th June 2015) - Shanks, T.; Metcalfe, N.; Chehade, B.; Findlay, J. R.; Irwin, M. J.; Gonzalez-Solares, E.; Lewis, J. R.; Yoldas, A. Kupcu; Mann, R. G.; Read, M. A.; Sutorius, E. T. W.; Voutsinas, S.
Abstract : The VLT Survey Telescope ATLAS survey is an optical ugriz survey aiming to cover ≈4700 deg 2 of the southern sky to similar depths as the Sloan Digital Sky Survey (SDSS). From reduced images and object catalogues provided by the Cambridge Astronomical Surveys Unit, we first find that the median seeing ranges from 0.8 arcsec FWHM (full width at half-maximum) in i to 1.0 arcsec in u, significantly better than the 1.2–1.5 arcsec seeing for SDSS. The 5σ mag limit for stellar sources is r AB = 22.7 and in all bands these limits are at least as faint as SDSS. SDSS and ATLAS are more equivalent for galaxy photometry except in the z band where ATLAS has significantly higher throughput. We have improved the original ESO magnitude zero-points by comparing m < 16 star magnitudes with the AAVSO Photometric All-Sky Survey in gri, also extrapolating into u and z, resulting in zero-points accurate to ≈ ± 0.02 mag. We finally compare star and galaxy number counts in a 250 deg 2 area with SDSS and other count data and find good agreement. ATLAS data products can be retrieved from the ESO Science Archive, while support for survey science analyses is provided by the OmegaCAM Science Archive, operated by the Wide-Field Astronomy Unit in Edinburgh.